2018
DOI: 10.1055/s-0038-1660868
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Imaging following Minimally Invasive Repair of Pectus Excavatum Is Unnecessary

Abstract: These data suggest that increased repetitive imaging after an initial postoperative CXR does not affect clinical outcomes and may not be necessary after MIRPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…exposes patients to ionizing radiation. [7][8][9]14 Third, the low interobserver agreement between R1 and R2 is consistent with the low sensitivity of chest X-ray for pneumothorax detection. 26 However, it is important to note that the assessments made by R2 were retrieved from the radiological reports and were not made specifically focused on the research purpose of this study.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…exposes patients to ionizing radiation. [7][8][9]14 Third, the low interobserver agreement between R1 and R2 is consistent with the low sensitivity of chest X-ray for pneumothorax detection. 26 However, it is important to note that the assessments made by R2 were retrieved from the radiological reports and were not made specifically focused on the research purpose of this study.…”
Section: Discussionsupporting
confidence: 58%
“…First, lung ultrasound was associated with better inter‐reader agreement compared with chest X‐ray for recognizing small subclinical pneumothorax, regardless of the experience of the various figures involved. Second, the agreement between lung ultrasound operators and R1 was low, suggesting that the use of postoperative chest X‐ray is of limited clinical value and unnecessarily exposes patients to ionizing radiation 7‐9,14 . Third, the low inter‐observer agreement between R1 and R2 is consistent with the low sensitivity of chest X‐ray for pneumothorax detection 26 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thirty-eight studies reported chest X-rays to be low-value, while four studies reported on low-value use of chest CT [ 78 – 117 ]. Of these, eighteen reported on chest X-rays in follow-up after procedures known to cause pneumothorax, where the X-ray did not change management in patients without symptoms [ 94 112 ]. Further, routine chest X-ray was found to not change patient management when used as a pre and post op screening, at hospital admission, in medical check-ups, or in staging of cervical and breast cancer.…”
Section: Resultsmentioning
confidence: 99%